Pemanfaatan Tepung Kulit Pisang Kepok (Musa paradisiaca linn) dalam Pembuatan Brownies - Oktavia Gita Hidiarti; Mia Srimiati (Sarana Ilmu Indonesia (salnesia), 2019)
Banana peel flour is a by-product of processed bananas that have not been widely used. Brownies is a food that is loved by many people from the age of children to adulthood. The aimed of this study was to analyse the effect of substitution of Kepok banana peel flour on the formulation of brownies. There were 4 treatments of the formulation, consists of: F0 (without banana peel flour), F1 45%, F2 50% and F3 55%. All of the formula were tested organoleptically, the test including colour, flavour, aroma, and texture. Furthermore, the best formula compared with the control (F0) on the proximate level. Based on the organoleptic test, the best formula was F1 (45% banana peel flour), this product has 32.99% of water content, 1.37% of ash, 15.04% of fat, 5.93% of protein, 44.67% of carbohydrates, and 1.51% of fiber. The control formula (F0), contain 31.18% of water, 0.73% of ash, 12.23% of fat, 8.22% of protein, 47.64% of carbohydrate, and 1.55% of fiber. Based on t-test, the water content, ash, fat, protein and carbohydrate of control formula (F0) and F1 (45% banana peel flour) were different statistically (P<0.05). We conclude that, banana peel flour can be used to substitute wheat flour until 45%, also can be used to make other product that similar with brownies.